2022
DOI: 10.1161/svin.121.000174
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy Versus Medical Therapy for Acute Stroke Attributable to Isolated Cervical Internal Carotid Artery Occlusion Without Intracranial Large Vessel Occlusion

Abstract: Background The optimal treatment for acute stroke attributable to isolated cervical internal carotid artery occlusion without intracranial target is unclear. The purpose of our study was to examine whether endovascular therapy for acute stroke attributable to isolated cervical internal carotid artery occlusion was associated with improved clinical outcome. Methods We identified patients from 2 comprehensive stroke centers during the period January 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, in the absence of these CML, a thromboembolic cause should be considered. In such cases, treatment options may include mechanical thrombectomy using aspiration and stent retrievers or aspiration alone for thrombus removal [12,13]. Therefore, a correct diagnosis is necessary for careful procedure preparation and for the selection of suitable devices [12,21,[33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the absence of these CML, a thromboembolic cause should be considered. In such cases, treatment options may include mechanical thrombectomy using aspiration and stent retrievers or aspiration alone for thrombus removal [12,13]. Therefore, a correct diagnosis is necessary for careful procedure preparation and for the selection of suitable devices [12,21,[33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is the leading cause of extracranial or tandem ICA occlusions, whereas thromboembolism more often causes intracranial occlusion [5,11]. Nevertheless, oversized thromboembolisms can affect the cervical segment or the origin of the ICA [13,14]. Dissections, on the other hand, predominantly impact the distal cervical segment of the ICA near the base of the skull [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an analysis of the MR CLEAN registry and MR CLEAN trial showed favorable outcomes in 54% of EVT-treated and 10% of non-EVT-treated patients with isolated distal ICA occlusion [ 9 ]; however, due to the low number of patients ( n = 41 EVT and n = 10 non-EVT), no regression analyses or statistical tests were performed. Another recent study showed a good clinical outcome in 73% of patients treated with EVT compared with 61% of patients treated with BMT in a cohort of 73 patients (OR 1.7; 95% CI 0.64–4.6) [ 10 ]; however, only patients with isolated cervical ICA occlusion were included and the differences in baseline characteristics between treatment groups limited interpretation. Other studies focused only on one treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing EVT + BMT versus BMT in these patients are scarce or imbalanced [ 8 10 ]. Recently, one study investigated the benefit of initial BMT in patients with isolated ICA occlusion and reported a favorable outcome in 69% [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 As revascularization of acute carotid occlusion gained acceptance as a treatment option, other groups reported their results. 3 A 2022 meta-analysis comparing acute CAS in patients with a tandem lesion, reported higher functional outcome with acute CAS (90-day modified Rankin Scale score ≤2, odds ratio, 1.52 [95% CI, 1.19–1.95]) but increased risk of symptomatic intracranial hemorrhage (odds ratio, 1.97 [95% CI, 1.23–3.15]). 4 However, this meta-analysis did not differentiate the pathophysiology of the tandem lesion by atherosclerotic versus dissection etiologies.…”
mentioning
confidence: 99%